Theoretical Research of the Modification of Cycloidal Gear used in RV Reducer of Robot - Zhao Bo; Deng Xiaozhong; Li Tianxing; Su Jianxin (Jixie chuandong, 2015)
Aiming at the cycloidal gear used in RV reducer of robots,based on the concept of the single tooth without side clearance,the tooth surface equation of the cycloidal gear after modification is deduced by directly adding the second- order parabolic modification amount to the theoretical conjugate tooth profile along the normal direction. The modification amount of different meshing position on tooth profile curve could be flexibly controlled by controlling the tooth profile modification coefficient. The differences between the parabolic modification and the traditional modification method of the combination of isometric and travel distance,the proposed parabolic modification method is much closer to the complete conjugate tooth profile on the main meshing areas.The TCA program of cycloidal- pinwheel transmission which is written in Matlab formed parabolic transmission errors and the correctness of this modification is proved,which provides a new thought for the modification design of cycloidal gear used in RV reducer.